2010
DOI: 10.1007/s10552-010-9694-3
|View full text |Cite
|
Sign up to set email alerts
|

HPV testing for cervical cancer screening appears more cost-effective than Papanicolau cytology in Mexico

Abstract: ObjectiveTo determine the incremental costs and effects of different HPV testing strategies, when compared to Papanicolau cytology (Pap), for cervical cancer screening in Mexico.MethodsA cost-effectiveness analysis (CEA) examined the specific costs and health outcomes associated with (1) no screening; (2) only the Pap test; (3) only self-administered HPV; (4) only clinician administered HPV; and (5) clinician administered HPV plus the Pap test. The costs of self- and clinician-HPV testing, as well as with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 38 publications
(35 reference statements)
2
31
0
4
Order By: Relevance
“…18 Moreover, it was reported that PAP combined with HPV test increases the capability to identify cervical cancer 13,19,20 .…”
Section: Concurrent Infectionsmentioning
confidence: 99%
“…18 Moreover, it was reported that PAP combined with HPV test increases the capability to identify cervical cancer 13,19,20 .…”
Section: Concurrent Infectionsmentioning
confidence: 99%
“…Increasing the uptake of cervical cancer screening is especially important because even though the ICER of adding vaccination to the Pap smear screening would be an cost-effective option, women of low socioeconomic status are less likely to participate in screening or to be able to afford the vaccination (Konno et al, 2008;Park et al, 2011;Praditsitthikorn et al, 2011;Yamamoto et al, 2012). The cost-effectiveness of vaccination in combination with frequent or infrequent screening by the NCSP needs to be evaluated, in light of young women's low screening participation rate and :http://dx.doi.org/10.7314/APJCP.2013.14.7.4329 Cost-Effectiveness of Cervical Cancer Screening Recently, the HPV-DNA screening test has attracted public attention, especially in developing countries, as a potentially more cost-effective alternative to the Pap smear (Levin et al, 2010;Flores et al, 2011). It may not be feasible for all women to receive regular Pap smears throughout their lives.…”
Section: Discussionmentioning
confidence: 99%
“…It may not be feasible for all women to receive regular Pap smears throughout their lives. Moreover, although the Pap smear is inexpensive, it is less accurate than the HPV-DNA test; therefore, screening at wider intervals with the highlysensitive HPV-DNA test may be more cost-effective than the current system (Gravitt et al, 2010;Levin et al, 2010;Chen et al, 2011;Flores et al, 2011;Shi et al, 2011). While HPV-DNA tests are not covered under the current NCSP, previous studies comparing screening methods have reported that the sensitivity of the Pap smear was improved markedly in combination with the HPV-DNA test (Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FDA and WHO have recommended these tests to be used in first-line primary screening. They can be used both in adjunct to cytology assays or alone for screening purpose [32]. Other mentioned tests are in the process of validation on large and small cohorts but they still need approval from FDA and other relevant governing bodies.…”
Section: Molecular Testing Of Hpvmentioning
confidence: 99%